Genetic predisposition of donors affects the allograft outcome in kidney transplantation: Single-nucleotide polymorphism of aquaporin-11 - Ji In Park; Seung Hee Yang; Jung Pyo Lee; Seong Ho Yoo; Yon Su Kim (The Korean Society of Nephrology, 2015)
Background: Aquaporin-11 (AQP11) is a novel member of the aquaporin family. Disruption of the murine Aqp11 gene causes severe proximal tubular injury and renal failure. The rs2276415 (G>A) single-nucleotide polymorphism in the human AQP11 gene results in glycine to serine substitution in a functionally important domain. In this study, the role of the genetic predispositions of AQP11 rs2276415 (G>A) on renal allograft outcomes was evaluated. Methods: A total of 198 pairs of donors and recipients were enrolled in this study. Long-term graft survival was traced and clinical parameters that could have influenced graft outcome were collected through the electronic medical record system. Results: The genotype distribution and allele frequency of rs2276415 polymorphism were not different between donors and recipients. Despite similar allele frequencies between donors and recipients, the minor allele rs2276415 (GA+AA) of AQP11 from the donors, but not from the recipients, had a harmful effect on the graft survival compared with the wild-type donor (GG; P=0.029). This association was significant after adjusting for several risk factors including age, sex, human leukocyte antigen mismatch, donor type, hypertension, and diabetes mellitus (P=0.032). Conclusion: A donor-derived, not recipient-derived, genetic AQP11 polymorphism has different effects on graft outcome. Thus, the genetic influence from donors should be carefully considered for proper management of allografts after kidney transplantation.